Импульсный регулируемый электропривод с фазными электродвигателями - Шикуть Э. В. Эргард Васильевич; Крайцберг М. И. Меер Ицкович; Фукс П. А. Павел Авраамович; Газганов А. Э. Александр Эммануилович (Москва, Энергия, 1972)
Авт. указаны на обороте тит. л.